Monitoring Phytate Hydrolysis Using Serial Blood Sampling and Feather Myo-Inositol Levels in Broilers - Greene, Elizabeth; Mallmann, Barbara; Wilson, Jonathan W.; Cowieson, Aaron J.; Dridi, Sami (Frontiers in Physiology, 2020)
Phytate forms insoluble precipitates with various cations that are recalcitrant to digestion in poultry. Dietary supplementation with exogenous phytase has been shown to improve phytate solubility and digestibility and, in turn, improve animal growth performance. Although the kinetics of phytate hydrolysis by exogenous phytase are well described in vitro, the progression of the reaction in vivo is still not well defined. The aim of the present study was, therefore, to monitor the kinetic variation of myo-inositol levels in both circulation and feather following exogenous phytase supplementation. Four week-old male broilers were individually housed with ad libitum access to water and a standard commercial diet. Birds were maintained under environmental temperature of 24°C and 30% RH. Birds were cannulated in the cutaneous ulnar vein on the right wing and remained untouched for 3 days. On the day of the experiment, birds were randomly divided into three body weight-matched groups and fed either the control diet, the control diet-supplemented with myo-inositol (MYO) or Ronozyme HiPhos (0.06%, DSM Nutritional Products, Switzerland). Growing feathers and blood were collected at baseline and then every two hours for 30h post-prandially. Plasma and feather myo-inositol levels were determined by HPLC. Plasma and feather myo-inositol levels were significantly increased at 6h to 8h post-prandial. The mRNA abundances of INPP1, IP6K1, and ISYNA in the circulation were significantly down regulated at all periods compared to the baseline levels. IP6K2, IP6K3, and MINPP1 gene expression, however, was up regulated at 8h post-prandial and then returned to the baseline levels. In feathers, the expression of INPP1 was induced at 8h post-prandial and remained higher compared to the baseline. The expression of IP6K2, IP6K3, and MINPP1 was down regulated during the first 10h and then returned to baseline levels for the rest of the post-prandial period. Taken together, our data show that phytase modulates the expression of genes associated with myo-inositol metabolism and generates release of myo-inositol in both circulation and feather at 6-10h post-feeding. Feather myo-inositol concentration could be used as a non-invasive method to monitor phytate hydrolysis in praxis.